Receptor interacting protein kinase 3 is a critical early mediator of acetaminophen‐induced hepatocyte necrosis in mice - Ramachandran, Anup; McGill, Mitchell R.; Xie, Yuchao; Ni, Hong‐Min; Ding, Wen‐Xing; Jaeschke, Hartmut (Hepatology (Baltimore, Md.), 2013)
Acetaminophen (APAP) overdose is a major cause of hepatotoxicity and acute liver failure in the U.S., but the pathophysiology is incompletely understood. Despite evidence for apoptotic signaling, hepatic cell death after APAP is generally considered necrotic in mice and in humans. Recent findings suggest that the receptor interacting protein kinase 3 (RIP3) acts as a switch from apoptosis to necrosis (programmed necrosis). Thus, the aim of the current investigation was to determine if RIP3 is involved in APAP‐induced liver cell death. APAP (200‐300 mg/kg) caused glutathione depletion and protein adduct formation, oxidant stress, mitochondrial release of apoptosis inducing factor, and nuclear DNA fragmentation resulting in centrilobular necrosis in C57Bl/6J mice. Inhibiting RIP3 protein induction with antisense morpholinos in wild‐type animals or using RIP3‐deficient mice had no effect on protein adduct formation but attenuated all other parameters, including necrotic cell death, at 6 hours after APAP. In addition, cultured hepatocytes from RIP3‐deficient mice showed reduced injury compared to wild‐type cells after 24 hours. Interestingly, APAP‐induced mitochondrial translocation of dynamin‐related protein 1 (Drp1), the initiator of mitochondrial fission, was inhibited by reduced RIP3 protein expression and the Drp1 inhibitor MDIVI reduced APAP‐induced cell death at 24 hours. All of these protective effects were lost after 24 hours in vivo or 48 hours in vitro. Conclusion: RIP3 is an early mediator of APAP hepatotoxicity, involving modulation of mitochondrial dysfunction and oxidant stress. Controlling RIP3 expression could be a promising new approach to reduce APAP‐induced liver injury, but requires complementary strategies to control mitochondrial dysfunction for long‐term protection. (Hepatology 2013; 58:2099–2108)